Seismic response of various sites of the territory of Kyiv to seismic loads - О.В. Кендзера; Ю. В. Семенова (Геофизический журнал, 2021)
The research presented in the work aims to assess the seismic response of three different taxonometric sites, identified by the method of engineering and geological analogies within the territory of Kyiv, to seismic loads with different spectral content and peak amplitude from 0.01 g to 0.06 g. Assessment of the influence of local soil conditions on the intensity of earthquakes is an important task of earthquake-resistant design and construction. The soil layer at the base of the study site acts as a filter on seismic vibrations. It amplifies or attenuates the amplitude of the seismic wave propagating from the bedrock to the free surface. The paper considers the mechanisms of the possible amplification of seismic motions by various soil complexes and methods for calculating the seismic response to seismic loads of various intensities. As an analytical tool for analyzing the response of the taxonometric areas to seismic vibrations (seismic response), an equivalent linear analysis was used, which is comprehensively studied and widely used in engineering seismology. For the selected sites, models of soil strata were built, and graphs of changes with depth of peak shear strain and peak ground acceleration (PGA) were calculated, as well as predicted (expected with a given probability of non-exceeding) amplitude Fourier spectra of seismic motions in the upper layer and the response spectra of single oscillators with 5 % attenuation to seismic effects with a maximum amplitude from 0.01 g to 0.06 g. A comparative analysis of the change in the value of these parameters in individual sections of Kyiv is presented. It is shown that to assess the potential hazard from seismic ground motions during earthquakes, it is necessary to use the maximum number of design parameters that characterize the seismic hazard of specific areas and which are used to determine the seismic resistance of buildings and structures. The most complete seismic hazard for calculating the seismic stability of objects is set by the full vector of seismic motions deployed in time: calculated accelerograms, seismograms and velocigrams. The presented calculation results are planned to be used in solving methodological and practical problems of earthquake protection, which can be realized in different parts of the territory of Kyiv.